Implementation of Bruner's Theory to Improve the Concept Understanding of Numbers - Wibowo, Sigit; Fery Muhamad Firdaus (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
The low understanding of mathematical concepts at the elementary school level is a serious problem so that mathematics learning can run effectively. This study aims to measure the increase in elementary school students' conceptual understanding after applying Bruner's theory in learning mathematics. This type of research is Class Action Research. The research design used was developed by Kemmis and McTaggart where each activity cycle consists of four components, namely planning, implementation of action/treatment, observation, and reflection. The research results show that the application of Bruner's learning theory can improve the mathematics concept understanding ability. Improvement of the concept understanding ability occurs in each cycle. At the beginning of the observation, the average number of concept understanding abilities of students was 22.67%, then increased in cycle I by 44%, cycle II by 69.33%, and achieving expectations in cycle III by 88%. The successful application of Bruner's learning theory is also evidenced by the increased mastery of student learning outcomes. At the beginning of the cycle, only 28% of students passed, then increased in cycle I by 48% of students, cycle II by 72% of students, and achieving expectations in cycle III by 92%. Thus, the implementation of Bruner's theory can improve understanding of the concept of numbers in learning mathematics.